Common errors in blog writing among bachillerato students at a public institution in Loja, school year 2023-2024. - Cuenca Macas, Angel Israel (2024)
This study investigates common errors in blog writing among second-year bachillerato students at a public institution in Loja, Ecuador, during the 2023-2024 school year. The research aims to identify, classify, and determine the frequency of errors in students' blog posts. Employing a descriptive quantitative design, the study analyzed a corpus of 80 blog posts written by students of intermediate level. Data collection involved a paper-and-pencil method, where students wrote about their vacation experiences in 80-100 words. The error analysis was conducted using the surface modification taxonomy taxonomy, which categorizes errors into four types: omission, addition, misformation, and misordering. The UAM Corpus Tool software was utilized for error identification and classification. Results revealed that omission errors were the most prevalent (42.03%), followed closely by misformation errors (41.27%). Addition errors accounted for 13.24% of the total, while misordering errors were the least common at 3.45%. At the linguistic level, grammatical (morphological) errors were found to be the most problematic, particularly in the categories of omission and misformation. These findings provide essential understandings of the specific challenges faced by Ecuadorian EFL learners in this text gender and have implications for curriculum development and instructional strategies in EFL writing. Keywords: EFL writing, error analysis, blog writing, surface modification taxonomy